This changes everything -- ICT and climate change : what can we do? : 13th IFIP TC 9 International Conference on Human Choice and Computers, HCC13 2018, held at the 24th IFIP World Computer Congress, WCC 2018, Poznan, Poland, September 19?21, 2018, Proceedings /: what can we do? : 13th IFIP TC 9 International Conference on Human Choice and Computers, HCC13 2018, held at the 24th IFIP World Computer Congress, WCC 2018, Poznan, Poland, September 19?21, 2018, Proceedings. (2018) - Unknown
No abstract available